2011
DOI: 10.1182/blood-2011-03-343046
|View full text |Cite
|
Sign up to set email alerts
|

Increasing concentrations of prothrombin complex concentrate induce disseminated intravascular coagulation in a pig model of coagulopathy with blunt liver injury

Abstract: Despite increasing use of prothrombin complex concentrate (PCC) to treat hemorrhage-associated coagulopathy, few studies have investigated PCC in trauma, and there is a particular lack of safety data. This study was performed to evaluate PCC therapy in a porcine model of coagulopathy with blunt liver injury. Coagulopathy was induced in 27 anesthetized pigs by replacing approximately 70% blood volume with hydroxyethyl starch 130/0.4 and Ringer's lactate solution; erythrocytes were collected and retransfused. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 46 publications
5
92
0
Order By: Relevance
“…Two animals in the saline group had a singular lung arteriole thromboembolus of 1 to 2 mm in diameter, whereas 3 animals from the lower PCC dosing group had several thromboemboli each measuring 1 to 2 mm in diameter. 91 Interestingly in those receiving higher doses of PCCs (50 IU/kg), disseminated intravascular coagulation was observed based on the International Society of Thrombosis and Hemostasis criteria, 92 and all of these animals contained >4 mm of multiple lung arteriole thromboembolisms on autopsy. In addition, a net-like fibrinogen deposition was noted in the lung capillaries of the higher dosage group, which was present but not as well developed in the control and low-dosage animals.…”
Section: Point-of-care Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two animals in the saline group had a singular lung arteriole thromboembolus of 1 to 2 mm in diameter, whereas 3 animals from the lower PCC dosing group had several thromboemboli each measuring 1 to 2 mm in diameter. 91 Interestingly in those receiving higher doses of PCCs (50 IU/kg), disseminated intravascular coagulation was observed based on the International Society of Thrombosis and Hemostasis criteria, 92 and all of these animals contained >4 mm of multiple lung arteriole thromboembolisms on autopsy. In addition, a net-like fibrinogen deposition was noted in the lung capillaries of the higher dosage group, which was present but not as well developed in the control and low-dosage animals.…”
Section: Point-of-care Testingmentioning
confidence: 99%
“…In addition, a net-like fibrinogen deposition was noted in the lung capillaries of the higher dosage group, which was present but not as well developed in the control and low-dosage animals. 91 In an ongoing multicenter, randomized, controlled trial from The Netherlands, the utility of 4F-PCCs (Cofact) is being studied with respect to reducing allogeneic red blood cell transfusions during orthotopic liver transplantation in cirrhotic patients with INR ≥1.5 (PROTON Trial; Netherlands Trial Register: 3174). 93 …”
Section: Point-of-care Testingmentioning
confidence: 99%
“…The diagnosis of compromised thrombin formation remains challenging. Neither prolonged PT or aPTT, nor an extended clotting time in viscoelastic tests, sufficiently portrays the magnitude of thrombin generation [68,70]. Indeed, Dunbar and Chandler found that trauma patients with prolonged PT (> 18 s), which is suggestive of TIC, had a threefold higher thrombin generation compared with individuals with normal PT (p = 0.01) [68].…”
Section: Improvement In Thrombin Generationmentioning
confidence: 99%
“…Innerhofer et al have recently shown in a prospective cohort study that prothrombin complex concentrates (PCC) are effective in correcting coagulopathy and reducing the need for transfusion in patients with severe blunt trauma [26]. However, larger randomized trials need to be conducted to evaluate this effect since an increased risk of thromboembolic events has been reported in the past as well [27]. We believe until that time has come, it is safer and more useful to have an uniform protocol.…”
Section: Massive Transfusion Of Blood Productsmentioning
confidence: 99%